Hop-Limit Path Mapping Algorithm for Virtual Network Embedding - Zhang, Min; Tang, Xijie (Wireless personal communications, 2017)
Virtual network (VN) mapping which deals with the allocation of network resources from the shared physical substrate to individual VNs is one of the key challenges for the application of realizing network virtualization. While a variety of state-of-the-art algorithms have attempted to address this issue from different aspects, the challenge still remains for mapping virtual link with hop count constraint. This paper presents a fast approximation path mapping algorithm to address this issue by formulating such virtual link mapping problem as a path-flow mathematical programming model, which aims to minimize the maximum link load factor. Through the use of the primal–dual method, a fully polynomial time approximation algorithm is proposed to solve this model. The experimental results show that the proposed algorithm can effectively solve the problem of path mapping with hop limit.